Identifying novel fungi species with therapeutic potential - Khan, Sulaiman; Farah Hanani, Zulkifli (CRC Press, 2025)
This chapter focuses on advanced approaches toward the discovery of new fungal species, with corresponding drug applications. Focusing on the great diversity of fungi, the chapter underlines their role in medicine and biotechnology. Different strategies for obtaining and identifying new fungal species are described, from the more conventional light microscopy and scanning electron microscopy to the more sophisticated molecular, chemometric, and computational methods. Issues in assessing therapeutic promise are discussed together with the information on HTS and in silico prediction of biologic activity. Examples from the real world and case studies highlight innovation and that fungi have huge potential in sectors such as health care, environmental industries, and more. New trends of fungi use, for instance, in renewable energy, are also discussed. Last of all, the chapter offers prospects for the development of fungal biotechnology to consolidate advancements in drug discovery and therapeutics.